The Racial Politics of Place in Faith-Based Social Service Provision. (29th January 2020) - Bolger, Daniel
Abstract: Prior research indicates that faith-based social service providers are overrepresented in disadvantaged neighborhoods, which has led some to advocate for their increased involvement in the U.S. social safety net. Yet, we have little understanding of how they and other social service organizations understand the significance of place in their work. Here I explore how conceptions of place matter for social service provision by drawing on 12 months of ethnographic observation and interviews with 24 key informants in two faith-based social service organizations in Houston, Texas. I find that faith-based organizations attach significance to their geographic location based not only on their proximity (or lack thereof) to their target service recipients, but also through relationships with key stakeholders. Agencies label places as safe or unsafe to recruit donors and volunteers, but in doing so they channel resources unequally between communities in ways that perpetuate racial disparities in social service access. The results have implications for understanding the importance of place within social service organizations, particularly faith-based agencies, which are increasingly relied upon to serve the urban poor.